COMPARATIVE ANALYSIS OF THE CLASSIFICATION OF HEALTH STATUS BY ARTIFICIAL INTELLIGENCE METHODS - Tyulepberdinova Г.А.; Mansurova М.Е.; Gusmanova Ф.Р.; Nurakhanova А.А.; Barakhnin В.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article considers one of the problems that does not lose its significance for the characteristics of the state of human health. The fact that an application for working with artificial intelligence algorithms using the determinants of the international classification of the functioning of several body functions has not yet been developed indicates the importance of this project to create a digital health profile. In this article, we will study the International Classification of Functioning and artificial intelligence algorithms that allow it to be used. We will consider the work on classifying the obtained data by classes according to the determinants of the international classification of functioning using artificial intelligence algorithms, comparing forecast models and further optimization to create the most suitable classification model. The article presents the study of the main methods of data processing, statistics related to the state of human health from the database under consideration, and a set of machine learning methods, information search methods. It is planned to study the problems and algorithms of data analysis and their application to solve problems of the state of human health.